The 'Birth of Doubt' and 'The Existence of Other Possibilities': Exploring How the ACAD Toolkit Supports Design for Learning - Carvalho, Lucila; Castañeda, Linda; Yeoman, Pippa (University of Alicante, 2023)
The circumstances in which humans live and learn are subject to constant change. Given these cycles of change, educational designers (teachers, instructional designers, and others) often search for new models and frameworks to support their work, to ensure their designs are in alignment with valued forms of learning activity. Our research foregrounds the entanglement of people (the relational), tasks (the conceptual) and tools (the digital and material) in formal and informal learning settings. In this paper, we explore the use of the ACAD toolkit with the aim of understanding how this analytical tool supports design for learning. A thematic analysis of five workshops attended by 40 educators from diverse professional and academic backgrounds in Spain and Argentina, reveals how ACAD supports educational designers in four distinctive ways: encouraging dynamic engagement with key elements and concepts; supporting the visualization of (dis)connections and (in)coherence in designs; prompting critical reflection on past practices and contexts; and stimulating discussion about future teaching practices. A key contribution of this article is the discussion about how the ACAD toolkit helps educators see the ways in which all learning is situated, subject to constraints and affordances at multiple scale levels, and oriented towards certain pedagogical purposes or values.
Keywords: Learning design; Design for learning; Educational design; Academic professional development; Diseño didáctico; Diseño para el aprendizaje; Diseño educativo; Desarrollo profesional docente